Geographic Information System For The Mapping Of Value Land Zone Of District Bengkong Based On AHP Analysis - Vera Astutik; Sudra Irawan; Wenang Anurogo (Politeknik Negeri Batam, 2017)
Information on the value of land in Indonesia is still very minimal and difficult to be known by the public, particularly in the area of Bengkong, it also results in the presence of new activity for land speculators who want to grab a great adventage in providing price and land value pricing-related information. The purpose of this research are to create the value land zone map (VLZ) that illustrates the value of land is relatively the same as delivering lines and different colors on each value owned and accompanied the factors whisch affected it, as well as presenting a price comparison between the village and the land on map in the form of the web. Spatial analysis and AHP can be used for weighting for the most influential parameters and has no effect, so that the AHP can be useful to assist in decision making. VLZ obtained by observation in the field using a questionnaire and interview against the respondent. Observation and interviews done with the technique of sampling purposisive namely the selection of the sample with the groups in the number of smallest unit of score. Samples taken as many as 25 in order to achieve an accurate data. The value of the acquired land price is the current value of land prices. The result of the research in the form of web map VLZ with 6 classification of land price, the prices that Bengkong area concertrated settlement areas as Rp 3.500.000/sqm for the land prices are the highest in the village of Sadai and Rp 327.000/sqm for the lowest land price was in the village of Tanjung Buntung.